1998
DOI: 10.1148/radiology.206.2.9457185
|View full text |Cite
|
Sign up to set email alerts
|

Cancellous bone volume and structure in the forearm: noninvasive assessment with MR microimaging and image processing.

Abstract: Histomorphometric parameters characterizing cancellous bone in the distal radius can be derived from in vivo MR microimages and are predictive of vertebral deformity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
137
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 187 publications
(140 citation statements)
references
References 0 publications
2
137
0
1
Order By: Relevance
“…Hwang et al (125) showed on the basis of micro-MRI data obtained in specimens of human trabecular bone that spatial autocorrelation analysis, discussed later in more detail, can provide information on intertrabecular spacing and orientation without the need to resort to binary images. The method is therefore applicable to relatively low-resolution BVF images of the kind obtained in vivo (127). An application to 3D m-MR images from specimens of the distal human radius showed that two structural parameters could explain over 90% of the variation in Young's modulus for uniaxial loading while BVF accounted for 56% only.…”
Section: D Structure Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Hwang et al (125) showed on the basis of micro-MRI data obtained in specimens of human trabecular bone that spatial autocorrelation analysis, discussed later in more detail, can provide information on intertrabecular spacing and orientation without the need to resort to binary images. The method is therefore applicable to relatively low-resolution BVF images of the kind obtained in vivo (127). An application to 3D m-MR images from specimens of the distal human radius showed that two structural parameters could explain over 90% of the variation in Young's modulus for uniaxial loading while BVF accounted for 56% only.…”
Section: D Structure Analysismentioning
confidence: 99%
“…A further potential motivation is the study of the structural manifestations of metabolic bone disease such as renal osteodystropy (166). Evidence for these developments is the rapid growth of the clinical literature (8,83,84,127,145,165,(167)(168)(169)(170)(171)(172) and also, to a lesser extent, the increased use of CT to characterize TB (14)(15)(16)(173)(174)(175)(176)(177).…”
Section: Clinical Applications Of Trabecular Bone Microstructural Anamentioning
confidence: 99%
See 1 more Smart Citation
“…Some examples have been given recently (6,7,11); however, they did not employ partial autocorrelation functions to measure anisotropy. We considered the anisotropy of autocorrelation and performed an analysis of MR images of the calcaneus, a non-trivial task due to its very inhomogeneous morphology and the gradient correction necessary for the compensation of the inhomogeneous RF field of the surface coil.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we developed and improved operatorindependent texture analysis methods. Spatial autocorrelation analysis (SACA) has only rarely been used for image processing up to now (6,7). With respect to osteoporosis, the anisotropy of spatial autocorrelation functions is expected to give promising results, which will be described and discussed in this work.…”
mentioning
confidence: 99%